W-shaped mesogens and variations of their molecular structure. Issue 5 (9th April 2019) - Horčic, Martin; Svoboda, Jiří; Novotná, Vladimíra; Pochiecha, Damian
ABSTRACT: New bent-core liquid crystalline dimers with W-shaped molecular geometry have been prepared and studied. We have modified the dimer shape by variation of the connecting part between two bent-core units and changing the terminal chains (perfluoroalkyl, siloxanealkyl). Additionally, we have altered the inner bend angle value (120°, 60° and 148°) by utilization of different aromatic units. Mesomorphic properties of new dimers were established based on the texture observation in the polarizing microscope and DSC measurements. Moreover, x-ray structural analysis has been performed for selected dimers to confirm phase identification. For most of the studied dimers, nematic or columnar phases have been detected, for several compounds appearing in a nematic-columnar phase sequence on cooling from the isotropic phase. The studied dimers showed richer polymorphism than their monomeric counterparts. Graphical Abstract: